2011
DOI: 10.1039/c1cp21283d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of green-light photoluminescence of Ta2O5 nanoblock stacks

Abstract: In this study we have explored the structural, electronic, and photoluminescence (PL) properties of Ta(2)O(5) nanoblock stacks. The Ta(2)O(5) nanoblocks were synthesized by the hot filament metal-oxide vapor deposition (HFMOVD) technique and randomly arranged in large-area stacks. Field-emission scanning electron microscopy (FESEM) showed most of the stacking Ta(2)O(5) nanoblocks to be 21 nm wide. Energy dispersive spectroscopy (EDS) analysis verified the presence of only the elements Ta and O. X-Ray photoemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…The broad visible light emission band is ascribed to the electron transitions between the deep levels and the valence band89. The deep levels are created by structural defects, impurities, Zn residues, and oxygen vacancies127 within the bandgap, but mainly from the various oxygen vacancies74142. The electron transitions (or PL emissions) from the conduction band, donor states (indicated by brown dashed lines), and deep levels (indicated by deep blue lines) to the valence band for the semiconducting hollow ZnO nanoballoons are schematically illustrated in Fig.…”
Section: Photoluminescence Emission Mechanismsmentioning
confidence: 99%
“…The broad visible light emission band is ascribed to the electron transitions between the deep levels and the valence band89. The deep levels are created by structural defects, impurities, Zn residues, and oxygen vacancies127 within the bandgap, but mainly from the various oxygen vacancies74142. The electron transitions (or PL emissions) from the conduction band, donor states (indicated by brown dashed lines), and deep levels (indicated by deep blue lines) to the valence band for the semiconducting hollow ZnO nanoballoons are schematically illustrated in Fig.…”
Section: Photoluminescence Emission Mechanismsmentioning
confidence: 99%
“…In this study, we are able to synthesize large-area arrays of vertical-aligned 1D NiO nanorods using the hot-filament metal-oxide vapor deposition (HFMOVD) technique. This technique has become very important, because it can be used to synthesize a variety of metal-oxide101617181920212223242526 and metal27282930 nanostructures with diverse morphological features and crystalline traits. The 1D NiO nanorods thus produced were then characterized by field-emission scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), x-ray diffractometry (XRD) and ultraviolet-visible spectroscopy.…”
mentioning
confidence: 99%
“…We found that the surfaces of the films are relatively smooth, but we could not observe clear differences between the surfaces. Some trap levels and shallow centres of oxygen vacancies in the bandgap of Ta 2 O 5 corresponding to light emission ranging from green to red wavelengths have been reported [10][11][12]. In addition, light emission ranging from blue to red wavelengths was also observed from Y 2 O 3 [13].…”
Section: O M / R E S U L T S -I N -P H Y S I C Smentioning
confidence: 89%